Point-of-care Ultrasound Diagnosis of Cardiac Myxoma - Joseph Brutico; Daniel Kreider (Clinical Practice and Cases in Emergency Medicine)
Introduction: Cardiac myxomas are rare benign tumors of the heart that can become clinically relevant due to cardiovascular effects. Diagnosis can be challenging due to non-specific presenting symptoms. Point-of-care ultrasound (POCUS) provides a convenient first-line screening modality. Case Presentation: A 65-year-old male with a history of tobacco use presented to the emergency department (ED) with a month of progressive dyspnea with exertion and hematemesis. Cardiac POCUS and pulmonary computed tomography with angiography revealed a left atrial mass consistent with a cardiac atrial myxoma. The patient underwent coronary artery bypass grafting with excision of the left atrial myxoma via right atriotomy and atrial septal defect repair. Discussion: Presented is a case of a patient presenting with progressive dyspnea diagnosed with a cardiac myxoma using POCUS in the ED. Cardiac myxomas have a wide variety of clinical presentations, and emergency physicians must maintain a high index of suspicion. Point-of-care-ultrasound is well suited for early diagnosis of this unique pathology. Surgical resection and tumor histopathology remain the mainstay of treatment.